The effect of public health-oriented drug law reform on HIV incidence in people who inject drugs in Tijuana, Mexico: an epidemic modelling study. (September 2018) - Borquez, Annick; Beletsky, Leo; Nosyk, Bohdan; Strathdee, Steffanie A; Madrazo, Alejandro; Abramovitz, Daniela; Rafful, Claudia; Morales, Mario; Cepeda, Javier; Panagiotoglou, Dimitra; Krebs, Emanuel; Vickerman, Peter; et al.
Summary: Background: As countries embark on public health-oriented drug law reform, health impact evaluations are needed. In 2012, Mexico mandated the narcomenudeo reform, which depenalised the possession of small amounts of drugs and instituted drug treatment instead of incarceration. We investigated the past and future effect of this drug law reform on HIV incidence in people who inject drugs in Tijuana, Mexico. Methods: In this epidemic modelling study, we used data from the El Cuete IV cohort study to develop a deterministic model of injecting and sexual HIV transmission in people who inject drugs in Tijuana between 2012 and 2030. The population was stratified by sex, incarceration status, syringe confiscation by the police, HIV stage, and exposure to drug treatment or rehabilitation (either opioid agonist treatment or compulsory drug abstinence programmes). We modelled the effect of these exposures on HIV risk in people who inject drugs, estimating the effect of observed and potential future reform enforcement levels. Findings: In 2011, prior to the narcomenudeo reform, 547 (75%) of 733 people who inject drugs in the El Cuete cohort reported having ever been incarcerated, on average five times since starting injecting. Modelling estimated the limited reform implementation averted 2% (95% CI 0·2–3·0) of new HIV infections in people who inject drugs between 2012 and 2017. If implementation reduced incarceration in people who inject drugs by 80% from 2018 onward, 9% (95% CI 4–16) of new HIV infections between 2018 and 2030 could be averted, with 21% (10–33) averted if people who inject drugs were referred to opioid agonist treatment instead of being incarcerated. Referral to compulsory drug abstinence programmes instead of prison could have a lower or potentially negative impact with −2% (95% CI −23 to 9) infections averted. Interpretation: Mexican drug law reform has had a negligible effect on the HIV epidemic among people who inject drugs in Tijuana. However, appropriate implementation could markedly reduce HIV incidence if linked to opioid agonist treatment. Unfortunately, compulsory drug abstinence programmes are the main type of drug rehabilitation available and their expansion could potentially increase HIV transmission. Funding: National Institute on Drug Abuse, UC San Diego Center for AIDS Research.